Larvicidal Activity of Essential Oils from the Leaves and Fruits of Nutmeg (Myristica fragrans Houtt) Against Aedes aegypti (Diptera: Culicidae) - Anne Carolina; Maman Maman (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this research was to examine the larvicidal activity of essential oil (EO) extracted from nutmeg (Myristica fragrans Houtt) leaves and fruits by steam distillation, and to analyze its chemical compounds. The EO yield of nutmeg leaves and fruits collected from the same tree was 0.66% and 0.30%, respectively. Larvicidal tests with the EO were carried out against Aedes aegypti (L.) (Diptera: Culicidae). The concentrations of nutmeg EO used for the larvicidal assay were 50, 100, 150, 200, and 250 μg/mL. The results showed that fruit oil was more toxic than the leaf oil. LC50 values of leaf and fruit EOs were 133.8 and 110.1 µg/mL, respectively. The chromatogram of GC-MS showed that the chemical components in nutmeg leaf and fruit EOs were dominated by α-pinene, sabinene, β-pinene, delta-3-carene, limonene, β-phellandrene, α-terpinolene, linalool, safrole, croweacin, and myristicin.